2014
DOI: 10.1074/jbc.m114.584649
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Membrane-targeting Domain of the Transient Receptor Potential Canonical (TRPC)4 Channel Unrelated to Its Formation of a Tetrameric Structure

Abstract: Background: Functional TRPC4/5 channels make tetrameric structures in the plasma membrane. Results: The 21-30 motif of TRPC4/5 regulates the membrane expression of the channels by interacting with PI(4,5)P 2 . Conclusion: The 21-30 motif of TRPC4/5 has an essential role in the membrane expression that does not involve the tetrameric structure. Significance: Our findings indicate the membrane expression regulating domain of TRP channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…The I-V curve showed a typical doubly rectifying shape, consistent with previous reports (Fig. 3B) [2324252627]. The current at -60 mV increased from -10.…”
Section: Resultssupporting
confidence: 91%
“…The I-V curve showed a typical doubly rectifying shape, consistent with previous reports (Fig. 3B) [2324252627]. The current at -60 mV increased from -10.…”
Section: Resultssupporting
confidence: 91%
“…In this context, TRP tetramerization involves transmembrane segments (Hellwig et al, 2005), ARD (Arniges et al, 2006;Erler et al, 2004;Hellwig et al, 2005), and different regions of the N tails (Chang et al, 2004;Myeong et al, 2014;Pertusa et al, 2014) and C tails (Becker et al, 2008;Erler et al, 2006;Hellwig et al, 2005;Lei et al, 2013;Zhang et al, 2011), including the TRP box (GarciaSanz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to prestin, Ibsen and colleagues demonstrated that the mechanosensitive ion channel, TRP-4, is required for ultrasound-mediated mechanical stimulation and can modify animal behaviour in the presence of MBs 16 . To test whether TRP-4 can act as an ultrasound-responsive protein, we transfected HEK293T cells with two members of the mammalian TRPC4 family including human TRPC4α (hTRPC4α) use TRPC4β (mTRPC4β) 27,28 . The calcium response of cells expressing hTRPC4α or mTRPC4β tagged with CFP upon FUS stimulation of different frequencies was examined and quantified.…”
Section: Resultsmentioning
confidence: 99%